Response of tifton 85 to nitrogen doses and cutting intervals - Alvim, Maurilio José; Xavier, Deise Ferreira; Venerque, Rui da Silva; Brotel, Milton de Andrade (Pesquisa Agropecuaria Brasileira, 1999)
This experiment was carried out at Embrapa-Centro Nacional de Pesquisa de Gado de Leite, located in Juiz de Fora, MG, Brazil, from October, 1995 to October, 1997, to evaluate the effects of five N doses (0, 100, 200, 400 and 600 kg/ha/year) and three cutting intervals (two, four and six weeks, during the rainy season, and four, six and eight weeks, during the dry season) on dry matter production and crude protein content of tifton 85. Data were analyzed as randomized blocks design in split-plot, with three replicates. The annual dry matter yield increased up to the highest dose of 600 kg/ha/year of N fertilization and up to four weeks cutting interval, during rainy season, and six-week cutting intervals, during the dry season. The highest production of dry matter was 23.1 ton/ha/year, of which 17.8 ton/ha were obtained in the rainy season. The lowest production was 2.6 ton/ha/year, of which 1.9 ton/ha were obtained in the rainy season. Crude protein content varied inversely with cutting intervals and as the amount of N fertilization increased up to dose of 600 kg/ha/year. The crude protein contents did not differ significantly with cutting intervals during the raining season. The highest level of crude protein obtained was 21.7%. Tifton 85 persistency was hampered in the absence of N fertilization and the shortest cutting interval.